Protective effect of DA-9401 in finasteride-induced apoptosis in rat testis: inositol requiring kinase 1 and c-Jun N-terminal kinase pathway - Soni KK; Shin YS; Choi BR; Karna KK; Kim HK; Lee SW; Kim CY; Park JK (Dove Medical Press, 2017)
Kiran Kumar Soni,1,* Yu Seob Shin,1,* Bo Ram Choi,1 Keshab Kumar Karna,1 Hye Kyung Kim,2 Sung Won Lee,3 Chul Young Kim,4 Jong Kwan Park1 1Department of Urology, Chonbuk National University and Research Institute of Clinical Medicine of Chonbuk National University-Biomedical Research Institute and Clinical Trial Center of Medical Device of Chonbuk National University, Jeonju, 2College of Pharmacy, Kyungsung University, Busan, 3Department of Urology, Samsung Medical Center, Samsung Biomedical Research Institute, Sungkyunkwan University Medical School, Seoul, 4College of Pharmacy, Hangyang University, Ansan, Republic of Korea *These authors contributed equally to this work Abstract: Finasteride is used to treat male pattern baldness and benign prostatic hyperplasia. This study investigated the toxicity of finasteride and recovery by DA-9401 using Sprague Dawley (SD) rats. Forty adult male SD rats were assigned to four groups: control (CTR), finasteride 1 mg/kg/day (F), finasteride 1 mg/kg + DA-9401 100 mg/kg/day (F + DA 100) and finasteride 1 mg/kg + DA-9401 200 mg/kg/day (F + DA 200). Treatments were by oral delivery once daily for 90 consecutive days. The gross anatomical parameters assessed included: genital organ weight; vas deferens sperm count and sperm motility; testosterone, dihydrotestosterone (DHT) and malondialdehyde levels; and histological and terminal deoxynucleotidyl transferase enzyme mediated dUTP nick-end labeling (TUNEL) staining of testis for spermatogenic cell density, Johnsen’s score and apoptosis. Testicular tissue was also used for evaluating endoplasmic reticulum (ER) stress and apoptotic proteins. Epididymis weight, seminal vesicle weight, prostate weight, penile weight and vas deferens sperm motility showed significant differences between the F group and the CTR, F + DA 100 and F + DA 200 groups. There was no significant change in the testosterone level. DHT level decreased significantly in the F group compared with the CTR group. Testis tissue revealed significant changes in spermatogenic cell density, Johnsen’s score and apoptotic index. Western blot showed significant changes in the ER stress and apoptotic markers. Finasteride resulted in reduced fertility and increased ER stress and apoptotic markers, which were recovered by administration of DA-9401 in the SD rats. Keywords: finasteride, DA-9401, infertility, sperm, dihydrotestosterone, endoplasmic reticulum stress, apoptosis